Property Changes of Chopped Glass Fiber-Reinforced Sheet Molding Compound Composite in Acid-Base Environment - Qi Chen; Yazhong Xia; Jiuyang Yu; Tianyi Zhang; Bowen Liu; Yaonan Dai (International Journal of Polymer Science)
To investigate the influence of acid-base environments on the properties of chopped fiber-reinforced resin matrix composites, corresponding unsealed specimens were prepared. These specimens were immersed in sodium hydroxide, hydrochloric acid solution, and deionized water for varying durations, after which their mechanical properties and surface hardness were tested. Changes in chemical composition, as well as alterations in fiber and resin matrix, were observed from a microscopic perspective. The results indicate that fracture at the fiber/matrix interface and hydrolysis aging of the matrix are the primary reasons for degradation in the mechanical properties of the composite. After 28 days of immersion, the hardness retention rates were found to be 54.34%, 75.96%, and 74.15% for deionized water, NaOH solution, and HCl solution, respectively. Similarly, the retention rates of tensile strength were 56.99%, 51.97%, and 58.32%, respectively. These findings provide valuable insights for the application of chopped fiber-reinforced vinyl ester resin matrix composite materials in equipment designed in acid-base environments.